Suffering from a Critical Oversight: The Persecutions of 1 Peter within Modern Scholarship - Williams, Travis B. (Currents in biblical research, 2012)
Throughout the history of research, the topic of persecution has been one of the more heavily debated issues within the study of 1 Peter. At the moment, however, a general agreement has been reached concerning the nature of the readers’ problems. According to the modern consensus, the persecutions were localized and sporadic hostility consisting of verbal abuse and discrimination (i.e., ‘unofficial’ persecution). The present article will survey exactly how this consensus was reached, focusing particular attention on a key oversight which took place very early in the discussion. Our review will explore some of the significant effects which this omission has produced in the subsequent debate, while examining how a few of the most recent treatments have worked towards rectifying the situation.